2004
DOI: 10.1523/jneurosci.2025-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cerebellar Interpositus Nucleus in the Genesis and Control of Reflex and Conditioned Eyelid Responses

Abstract: The role of cerebellar circuits in the acquisition of new motor abilities is still a matter of intensive debate. To establish the contribution of posterior interpositus nucleus (PIN) to the performance and/or acquisition of reflex and classically conditioned responses (CRs) of the eyelid, the effects of microstimulation and/or pharmacological inhibition by muscimol of the nucleus were investigated in conscious cats. Microstimulation of the PIN in naive animals evoked ramp-like eyelid responses with a wavy appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 41 publications
10
102
1
2
Order By: Relevance
“…It is possible that lesion studies performed in the anterior interpositus (Yeo et al, 1985;Krupa et al, 2003) did affect axons originated in the posterior part of the nucleus. Moreover, as reported in previous studies (Gruart et al, 1995(Gruart et al, , 2000Trigo et al, 1999;Jiménez-Díaz et al, 2004), there are important functional differences between rabbits and cats. The more important is that the retractor bulbi system seems not to be involved in the generation of CRs in cats (Trigo et al, 1999).…”
Section: The Posterior Interpositus Nucleus As An Enhancer Of Acquirementioning
confidence: 52%
See 3 more Smart Citations
“…It is possible that lesion studies performed in the anterior interpositus (Yeo et al, 1985;Krupa et al, 2003) did affect axons originated in the posterior part of the nucleus. Moreover, as reported in previous studies (Gruart et al, 1995(Gruart et al, , 2000Trigo et al, 1999;Jiménez-Díaz et al, 2004), there are important functional differences between rabbits and cats. The more important is that the retractor bulbi system seems not to be involved in the generation of CRs in cats (Trigo et al, 1999).…”
Section: The Posterior Interpositus Nucleus As An Enhancer Of Acquirementioning
confidence: 52%
“…8). This phase-modulating device could play a damping role in eyelid performance, particularly during the process of acquiring new motor abilities (Jiménez-Díaz et al, 2004), a proposal already put forward by others (Thach et al, 1992). In this regard, it has been recently reported that disturbances in fast cerebellar oscillation in the cerebellar cortex could be related to cerebellar ataxia (Cheron et al, 2005).…”
Section: Phase-inversion Properties and Modulating Role Of Posterior mentioning
confidence: 92%
See 2 more Smart Citations
“…All the implanted electrodes were soldered to a socket fixed to the holding system. A detailed description of this chronic preparation can be found elsewhere (Trigo et al, 1999;Gruart et al, 2000;Jiménez-Díaz et al, 2004;Sánchez-Campusano et al, 2007).…”
Section: Methodsmentioning
confidence: 99%